Antifungal antibiotic of the Basidiomycete Oudemansiella mucida. II. Life cycle and fructification of the producing fungus - Musílek, V; Semerdzieva, M (Folia microbiologica, 1977)
The developmental cycle of the fungus Oudemansiella mucida, the producer of a new antifungal antibiotic, was found to be controlled by the mechanism of homogenic tetrapolar incompatibility; under our conditions, the cycle took about 12 weeks to completion. Optimum conditions for a laboratory-scale fructification were investigated. Normal fruiting body formation required sufficient illumination, temperatures below 20 degrees C, and relative humidity in excess of 70%. Flask-grown fruiting bodies did not differ from the naturally occurring ones. The basidiospores of the produced fruiting bodies yielded the reference monokaryons necessary for physiological, cytological and genetical studies.
Keywords: kultivační média; teplota; vlhkost; ponoření; Bacteriological Techniques; Immersion; Basidiomycota; Antifungal Agents; Temperature; Humidity; antifungální látky; bakteriologické techniky; Culture Media